ABOUT MECHANISM OF STRUCTURE FORMATION OF PARTICULAR SOLID CARBONIC PHASE IN NANOCOMPOSITE ON THE BASIS OF IRON AND NANO-DISPERSE CARBON - D. V. Kuis; N. A. Svidunovich; G. P. Okatova; V. S. Urbanovich; V. M. Oichenko (Литьë и металлургия)
The mechanism of structure formation in super-solid carbon phase in nanocomposite on the basis of iron and nano-disperse carbon, which can be used at development of technology and composition of creation of new materials using inexpensive nano-carbon materials is offered.